THE SPECIFIC FEATURES OF MODERNIZATION AND DIVERSIFICATION OF THE SERVICE SECTOR IN THE REPUBLIC OF UZBEKISTAN (International journal of medical sciences, 2026)
The article examines the specific features and challenges of modernization and diversification of the service sector in the Republic of Uzbekistan in the context of structural economic transformations and digital transformation. The growing role of the service sector as one of the key drivers of sustainable economic growth, employment, and enhancement of national economic competitiveness is substantiated. The main development trends in priority segments of the service sector, including tourism, financial and fintech services, information and communication technologies, transport, and logistics, are analyzed. Key constraints to modernization are identified, including regional disparities, infrastructural and human resource problems, as well as institutional barriers. The paper proposes directions for comprehensive modernization and diversification of the service sector based on digitalization, development of platform-based business models, institutional support for innovation, and investments in human capital.